Pengaruh Manajemen Laba terhadap Kinerja Keuangan pada Perusahaan Manufaktur Tahun 2011-2012 - Aminah AMINAH; Lidya Natasia Gunakan (Universitas Bandar Lampung (UBL), 2015)
This study aims to obtain empirical evidence about the effect of earnings management onfinancial performance. Earnings management is the act which is conducted by manager to maximize, minimize, or do income smoothing of company’s profit. Managers can affect their company’s market value by do earnings management, such as make their profit always increase every year to show their good financial performance. Indipendent variable of this study is earnings management that measured by discretionary accruals and dependent variable is financial performance that measured by return on asset and debt to equity ratio. This study use analysis of descriptive statistics, simple linier regression with t test and coefficient determination by SPSS 18 program. Samples of this study are 15 manufacturing companies obtained in Indonesia Stock Exchange (BEI) from 2011-2012 period. The results of this study showed that earnings management affect return on asset positive significantly and earnings management affect debt to equity ratio negative unsignificantly.